(untitled) (Archives of Clinical Psychiatry, 2011)
INTRODUCTION: The preservation of oral comprehension in the elderly is correlated with the preservation of their cognitive functions. Oral comprehension is a key feature for communication and its evaluation allows for the identification of more specific cognitive deficits, in addition to facilitating the development of more effective, early intervention strategies. OBJECTIVE: Provide contemporary standards for the use of an instrument to assess oral comprehension, the Token Test, in a sample of healthy seniors. METHOD: A sample of 120 patients (76 women) with mean age of 71.1 years and 6.9 years of formal education, was assessed using the Mini Mental State Examination to identify the existence of cognitive impairment, and the Token Test to assess oral comprehension. RESULTS: There were significant correlations (p < 0.01) between the token test scores for education and age, which accounted for 5% and 21% of shared variance, respectively. These two variables were considered on the normative data tables. DISCUSSION: The data obtained indicate that the standards provided here are sufficiently representative. This study identifies the need for future studies comparing the Token Test performance in elderly people either healthy or in the process of cognitive decline.